Christian Staerklé et Fabrizio Butera (éds). Conflits Constructifs, Conflits Destructifs. Regards Psychosociaux. Lausanne: Antipodes, 2017 - Peralta, Nadia Soledad (2017)
Fil: Peralta, Nadia Soledad. Universidad Nacional de Rosario; Argentina